A new approach to prealbumin as a biomarker for fibromyalgia? - Karabacak, Elif; Yayla, Muhtesem E.; Ozturk, Gulsah Y.; Ozelbaykal, Bahadir (Biomedical papers, 2025)
Aims. Fibromyalgia (FM) is a chronic, widespread musculoskeletal disease that is usually accompanied by hyperalgesia, fatigue, sleep disturbance and depression. Although the etiopathogenesis of this syndrome is unclear, it is presumed to have an inflammatory basis. There are currently no laboratory markers available to diagnose the condition. The aim of this study was to investigate potential biochemical markers that would prove to be valid, simple, routinely used, quickly and cheaply studied and obtainable in blood count tests.Methods. 46 patients diagnosed with FM according to ACR (American College of Rheumatology) 2010 diagnostic criteria and 35 patients as a healthy control group were included in the study. Prealbumin, complete blood count, sediment and C-reactive protein (CRP) values of FM and control group patients were examined. Additionally, Hospital Anxiety and Depression Scale, Jenkins Sleep Scale and the Fibromyalgia Impact Questionnaire (FIQ) were administered to patients diagnosed with FM.Results. There was a significant difference between fibromyalgia patients and control groups in terms of prealbumin, platelet, CRP, CRP/prealbumin and lymphocyte parameters (P=0.048, P=0.046, P<0.001, P=0.003 and P<0.001, respectively). Only a weak positive correlation was found between CRP and FIQ (rS =0.309, P=0.037, CI=0.012-0.556).Conclusion. The serum levels of some tested markers, including platelets, CRP, CRP/prealbumin and lymphocytes, were significantly higher and prealbumin was lower in patients with FM than in the control group, suggesting they could be valid in fibromyalgia diagnosis. The CRP level may be informative about the severity of the FM and it may play a role in the inflammation possibly underlying the pathogenesis of FM.
Keywords: CRP; CRP/prealbumin; lymphocyte; platelet; prealbumin